2014
DOI: 10.1002/jobm.201300647
|View full text |Cite
|
Sign up to set email alerts
|

Production of allitol from D‐psicose by a novel isolated strain of Klebsiella oxytoca G4A4

Abstract: A novel bacterium capable of producing allitol from D-psicose was isolated from soil and identified as Klebsiella oxytoca G4A4. An efficient method for the transformation of D-psicose to allitol was achieved through the resting cell reaction. Ribitol as an inducer is suitable for cell cultivation, and cells are most active in Tris-HCl buffer (pH 8.0) at 37 °C with a density of 40 (OD600 nm ). After the reaction, the final conversion rates of the washed cells were approximately 87, 83, and 55% at D-psicose conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Allitol is a six-carbon alcohol that can be used as a low-calorie sweetener and as a laxative for treatment of constipation. 3 -6 RDH has previously been produced from Aerobacter aerogenes, 7 Enterobacter agglomerans, 8 Gluconobacter oxydans, 4 Klebsiella aerogenes, 9 Rhodobacter sphaeroides, 10 Klebsiella oxytoca 11 and Zymomonas mobilis. 5 In a previous study the cloning, expression and characterization of a new RDH from Z. mobilis was reported as the first characterized recombinant RDH.…”
Section: Introductionmentioning
confidence: 99%
“…Allitol is a six-carbon alcohol that can be used as a low-calorie sweetener and as a laxative for treatment of constipation. 3 -6 RDH has previously been produced from Aerobacter aerogenes, 7 Enterobacter agglomerans, 8 Gluconobacter oxydans, 4 Klebsiella aerogenes, 9 Rhodobacter sphaeroides, 10 Klebsiella oxytoca 11 and Zymomonas mobilis. 5 In a previous study the cloning, expression and characterization of a new RDH from Z. mobilis was reported as the first characterized recombinant RDH.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, D-allulose could be spray-dried by the addition of excipients, which would be helpful for pulmonary drug delivery (Kawakami et al, 2013;Kawakami et al, 2014). Additionally, it is reported that D-allulose is the precursor of other hexoses and plays an extremely important role in the production of D-allose (Feng, Mu, & Jiang, 2013;Yeom, Seo, Kim, & Oh, 2011), D-allitol (Han et al, 2014), D-talitol (Sasahara, Mine, & Izumori, 1998), D-tagatose (Yoshihara, Shinohara, Hirotsu, & Izumori, 2006) and D-altrose (Menavuvu et al, 2006).…”
Section: Application Of D-allulosementioning
confidence: 99%
“…The Michaelis-Menten constants (K m ) of RDHs from K. aerogenes, Rhodobacter sphaeroides, E. agglomerans, G. oxydans, Z. mobilis, E. aerogenes and P. alcalifaciens with ribitol were 8, 6.3, 32.2, 1.2, 11.8, 10.3 and 13.9 mM, respectively (Kahle et al, 1992;Muniruzzaman et al, 1995b;Adachi et al, 2001;Moon et al, 2010;Han et al, 2014;Hassanin et al, 2015;Singh et al, 2015). No previous study has examined the kinetic parameters of reduction in D-psicose into allitol by RDH.…”
Section: Sources Of Rdhsmentioning
confidence: 99%
“…Use of this strain for production of allitol did not involve consumption of the substrate (D-psicose) (Muniruzzaman et al, 1995a). Han et al (2014) reported production of allitol from D-psicose using Klebsiella oxytoca G4A4 isolated from soil. Transformation was investigated using a resting cell reaction.…”
Section: Microbial Synthesis Of Allitolmentioning
confidence: 99%
See 1 more Smart Citation